Transformasi Kebijakan Kurikulum di Indoneisa: Studi Kepustakaan dari K13 ke Kurikulum Merdeka - Ibrahim, Ibrahim; Enjelita, Anggi; Aulia, Safira; Novansyah, M. Firdaus; Fatmawaty, Fatmawaty (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine changes in curriculum policy in Indonesia from the 2013 Curriculum to the Merdeka Curriculum through a literature review approach. The method employed is library research by analyzing national and international journals, academic books, research reports, and relevant policy documents. The data sources for this study were drawn from national and international scientific journals, academic books, education policy documents, research reports, and official regulations related to the 2013 Curriculum and the Merdeka Curriculum. Data analysis is conducted using a descriptive thematic approach to identify conceptual shifts, policy directions, and the implications of implementation at the educational unit level. The findings indicate that the implementation of the Merdeka Curriculum is a response to the need for learning that is more flexible, contextual, and learner-centered. This curriculum emphasizes teacher autonomy, differentiated learning, and the simplification of competency achievements, in contrast to the 2013 Curriculum, which tends to be more structural and administrative. The successful implementation of the Independent Curriculum is greatly determined by the readiness of educators, the availability of supporting facilities, and the consistency of policies. This curriculum transformation is a strategic step to improve the quality of education, although it still requires continuous guidance and evaluation